2021
DOI: 10.1159/000520328
|View full text |Cite
|
Sign up to set email alerts
|

G-8 Geriatric Screening Tool Independently Predicts Progression-Free Survival in Older Ovarian Cancer Patients Irrespective of Maximal Surgical Effort: Results of a Retrospective Cohort Study

Abstract: <b><i>Background:</i></b> We evaluated the prognostic impact of various global health assessment tools in patients older than 60 years with ovarian cancer (OC). <b><i>Methods:</i></b> G-8 geriatric screening tool (G-8 score), Lee Schonberg prognostic index, Eastern Cooperative Oncology Group (ECOG) performance status, and Charlson Comorbidity Index (CCI) were determined retrospectively in a consecutive cohort of elderly patients with OC. Univariate and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
(51 reference statements)
0
19
0
2
Order By: Relevance
“…As presented in Table 1 , nine cohort studies, including two prospective ( 23 , 28 ) and seven retrospective cohorts ( 21 , 22 , 24 27 , 29 ), with 2497 patients with OC contributed to the meta-analysis. These studies were published between 2017 and 2022, and performed in the United States ( 22 , 23 , 25 , 27 , 29 ), Italy ( 21 ), France ( 24 ), and Germany ( 26 , 28 ). All of the studies included patients with confirmed diagnosis of OC, and four studies included older patients only ( 21 , 24 , 26 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As presented in Table 1 , nine cohort studies, including two prospective ( 23 , 28 ) and seven retrospective cohorts ( 21 , 22 , 24 27 , 29 ), with 2497 patients with OC contributed to the meta-analysis. These studies were published between 2017 and 2022, and performed in the United States ( 22 , 23 , 25 , 27 , 29 ), Italy ( 21 ), France ( 24 ), and Germany ( 26 , 28 ). All of the studies included patients with confirmed diagnosis of OC, and four studies included older patients only ( 21 , 24 , 26 , 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, studies evaluating the correlation between frailty and survival of patients with OC showed inconsistent results ( 21 29 ). Some studies suggested that high frailty was associated with poor survival of these patients ( 22 , 24 , 25 , 27 29 ), while others failed to show a significant association ( 21 , 23 , 26 ). Therefore, we performed a systematical review and meta-analysis to comprehensively investigate the relationship between frailty and survival of patients with OC.…”
Section: Introductionmentioning
confidence: 99%
“…postoperative prognosis (54,55,58). Consecutively, the frailty status was seen as a potential confounder in this study and was included in the multivariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…These mainly preoperatively detectable parameters seemed to give important insights into the patients' prognosis regardless of the administration of RBC transfusions. Especially in older women with OC, a multilayered and interdisciplinary diagnostic or rehabilitation program might be helpful to enable an individual therapy concept mainly in frail patients, as G8-frail patients were faced with a poor prognosis irrespectively of maximal surgical effort (58). A moderate transfusion management, based on the fact that RBC transfusions in symptomatic anemic OC patients, was not associated with an overall poorer outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation